Diagnostic traps in orbital diseases - analysis and comparison of two cases - Mateusz Kamil Świątek; Paweł Ziemba; Ewa Jasiewicz; Hanna Dańków; Dorota Pojda-Wilczek (Śląski Uniwersytet Medyczny w Katowicach, 2022)
Proptosis is a characteristic sign that might suggest the diagnosis of different diseases. Proptosis is characterised by the anterior displacement of the eye and its protrusion. The most commonly associated symptoms of proptosis are deteriorated vision, elevated intraocular pressure and inflammation of periocular tissues. The presented study describes two cases of patients with proptosis and periocular pain. In each case, the primary cause of proptosis was initially incorrectly diagnosed and required in-depth diagnostics. In Patient A extrabulbar optic neuritis caused by Lyme disease was suspected and treated with steroids and antibiotics. Subsequently, Graves' disease was diagnosed and treated with anti-thymocyte globulin. Complete loss of vision was observed after one month of treatment. Radiotherapy and steroid therapy were introduced. Afterwards, the patient's vision was restored. Patient B, who was treated for hypothyroidism, was admitted to the hospital with elevated intraocular pressure, double vision, a restricted visual field and proptosis. The primary diagnosis was Graves' ophthalmopathy (GO). However, after in-depth imaging and pathomorphological studies of a specimen taken from the orbit, B-cell lymphoma was diagnosed. After the introduction of correct treatment, significant improvement was noted. Presented work indicates that in-depth diagnostics are crucial when it comes to the differential diagnosis of GO and a tumor of the orbital cavity.